The Potential Application Of Blind Write Protocol - Suryana, Nanna; Anshar, Khairul; Abdullah, Noraswaliza (Machine Intelligence Research Labs., 2018)
The current approach to handle interleaved write operation and preserve consistency in relational database system relies on locking protocol. The application system does not have other option to deal with interleaved write operation. In other hand, allowing more write operations to be interleaved will increase the throughput of database but it can result to an inconsistent database state. Since the application system has their own consistency and availability requirement then this paper proposes blind write protocol as a complement to the current concurrency control. Since blind write protocol will not lock any entity, then it should use read commited isolation level, auto commit, and request one read operation only to be used in consistency validation. Because, in between two read operations there could be another transaction perform blind write operation to the same entity. These two read operations which access the same entity may return different value